A user-friendly enterprise framework for data intensive Web applications - Garzotto, F. (IEEE International Conference on Information Reuse and Integration 2005, 2005)
The paper proposes an approach to enterprise frameworks for data intensive Web applications that is centered on the needs of "domain experts", who are specialists in a business or cultural sector but typically lack of technological expertise. We discuss our approach by presenting the requirements, design, and implementation of Medina, an enterprise framework for data intensive Web applications in the field of cultural tourism. Medina comprises: i) a user-friendly visual tool that can be used, without any implementation know-how, to customize and instantiate the framework, and to preview the effects of these operations; ii) a modular, highly portable software architecture that integrates the above tool and supports dynamic application preview and generation.